“TRENDS OF INNOVATIVE DEVELOPMENT IN THE REPUBLIC OF UZBEKISTAN” - Yuzbaeva Makhfuza Zakirjanovna; Mukumova Nargis Nuriddinovna; Charshanbieva Bakhtiniso Ural qizi (American Journals, 2023)
This article examines the role of innovation in the economic development of the country. Studied legal acts aimed at the development of domestic innovations.
Keywords: Innovation, innovative development, science, innovative products.